Toward a cultural psychology of collective action: Just how "core" are the core motivations for collective action?. (2019) - van Zomeren, Martijn
Abstract : I review the interesting contributions to this special thematic section in light of what has been referred to as the four core motivations for collective action (i.e. moral conviction, and group identification, anger and efficacy beliefs). Specifically, I relate the key findings and insights from these articles — based on intriguing data from participant samples in the Philippines, Japan, Indonesia and China — to these core motivations for collective action, after which I raise the question of just how "core" these motivations are, with an eye to an abundance of cultural variance. I answer this question by suggesting a number of conceptual bridges to move the field forward toward a proper cultural psychology of collective action. Such a cultural psychology, in my view, does justice not only to the notion of core motivations for collective action but also to the abundance of cultural variance. Specifically, I suggest to think about culture in terms of guiding when collective action is more or less likely to occur, within which the core motivations reflect the psychological processes that facilitate it.